Karel de Nerée tot Babberich’s Forgotten Torture Garden - Bink, Sander (The Rijksmuseum Bulletin, 2020)
In her standard work Het Symbolisme in de Nederlandse schilderkunst (1955) Bettina Polak regarded the oeuvre of C.K.H. de Nerée tot Babberich (1880-1909) as one of the highlights of fin de siècle Dutch art. A fine example is the pastel portrait of Henri van Booven as a Young Priest (1900-01) that the Rijksmuseum acquired in 2019. The museum’s collection already had nine sheets by Carel de Nerée in different techniques (pencil, ink and bodycolour). One of them, an allegorical scene of figures and a peacock in a garden, is striking in its relatively large size, the Symbolist style and the exotic subject. Based on technical characteristics of form and previously unknown or little studied sources, it is argued that the scene is based on Le Jardin des supplices (1899) by Octave Mirbeau. This novel was regarded as pornographic in the Netherlands, but it nonetheless inspired the contrarian young artist to create one of his first works, which proves to have been made between the summer of 1899 and the spring of 1901. In the article the drawing is placed in its biographical context and a number of other sheets by De Nerée from the collection are interpreted in more detail.